Educação e escolarização da criança indígena com deficência em Terra Indígena Araribá - Sá, Michele Aparecida de (2015)
The Brazilian educational policy about Special Education interfaced to Indigenous Education is still under construction. According to the Scholar Census of São Paulo state (BRAZIL, 2011) there are indigenous children with disabilities enrolled in indigenous schools in their communities. However, there is a dearth of studies on the education of indigenous children with disabilities. This study aimed to describe, analyze and understand the association between Special Education and the Indigenous education in Araribá indigenous land, São Paulo state. The specific aims of this study were: 1) Map the enrollment of indigenous students with disabilities in indigenous schools in Brazil; 2) Examine the structure of indigenous education in the State of São Paulo; 3) Identify the way that family and community (Nimuendajú and Tereguá) comprehend the disabled people and; 4) Identify and analyze the limits and possibilities of indigenous school Tereguá regard a student with disability. The study s theoretical framework was the historical-materialism. The methodological procedures were composed by semi-structured interviews with a teacher and two vice-directors of indigenous schools, a father and two mothers, two leaders and an elderly; there were observations in communities and schools; and documents analysis. The results of this study revealed that in the context of these indigenous communities, special education does not happen yet and the indigenous children with disabilities do not have access to the services offered by special education. However, this is not a specific event of indigenous schools of the Araribá s indigenous land. According to data from school census, there has been a significant increase in the enrollment numbers of indigenous children with disabilities in indigenous schools on entire country. Nevertheless, only a small number of indigenous students with disabilities in Brazil gets some type of care offered by special education, which demonstrates that there is no interest of government in this issue. Furthermore, there are other problems in indigenous schools in São Paulo state. It was identified government negligence in other areas, such as, absence of adequate study material in order to maintain their culture; Initial and continuous training are precarious; low financial investment; absence of financial investment in order to increase physical structure and quantity of schools; no scholar transportation; negligence in the execution and improvement of existing education policies. It has concluded that it is important to defend an emancipatory, critical and questioner educational practice guaranteed by the purpose of Historical-Critical Pedagogy, which defends the right of everybody to access to the cultural heritage historically developed. Through this pedagogical theory, the indigenous school could be a space where students with or without disabilities can own the systematized knowledge and admit a function beyond the reproduction of dominant social relations.